Gut microbe-derived metabolite trimethylamine N-oxide activates PERK to drive fibrogenic mesenchymal differentiation - Seok-Jo Kim; Swarna Bale; Priyanka Verma; Qianqian Wan; Feiyang Ma; Johann E. Gudjonsson; Stanley L. Hazen; Paul W. Harms; Pei-Suen Tsou; Dinesh Khanna; Lam C. Tsoi; Nilaksh Gupta; et al. (iScience, 2022)
Summary: Intestinal dysbiosis is prominent in systemic sclerosis (SSc), but it remains unknown how it contributes to microvascular injury and fibrosis that are hallmarks of this disease. Trimethylamine (TMA) is generated by the gut microbiome and in the host converted by flavin-containing monooxygenase (FMO3) into trimethylamine N-oxide (TMAO), which has been implicated in chronic cardiovascular and metabolic diseases. Using cell culture systems and patient biopsies, we now show that TMAO reprograms skin fibroblasts, vascular endothelial cells, and adipocytic progenitor cells into myofibroblasts via the putative TMAO receptor protein R-like endoplasmic reticulum kinase (PERK). Remarkably, FMO3 was detected in skin fibroblasts and its expression stimulated by TGF-β1. Moreover, FMO3 was elevated in SSc skin biopsies and in SSc fibroblasts. A meta-organismal pathway thus might in SSc link gut microbiome to vascular remodeling and fibrosis via stromal cell reprogramming, implicating the FMO3-TMAO-PERK axis in pathogenesis, and as a promising target for therapy.